Slovenian Catholic Church During the Second World War and the Govern of Marshal Tito [1941–1980] - Żurek, Piotr (Poznańskie Studia Slawistyczne, 2016)
The history of Slovenian Catholic Church is a field, which is not well known in Poland. That is why this article aims to present one of the peculiar episode from the past of Slovenian Catholicism. The article covers the time of the Second World War and the govern of marshal Tito. During the Second World War Slovenian Catholic Church existed under the occupation of the fascist countries – Italy and The Third Reich. In this period, the main offensive power was the communists, who were fighting against invaders and often had a negative attitude towards clergy. Their attitude resulted in collaboration of Slovenian catholic hierarchs with the communists. The communists’ governs established in 1945 and the consolidation of Tito’s power situated the Catholic Church in a new reality, which was Yugoslavian variant of communism called “Titoism”. This doctrine shaped terms of the existence of Slovenian Catholic Church until 1980 when the marshal Tito died and the Yugoslavia’s breakdown began.